Health and social consequences of an alcohol-related admission to critical care: a qualitative study. Issue 4 (5th April 2016) - McPeake, Joanne; Forrest, Ewan; Quasim, Tara; Kinsella, John; O'Neill, Anna
Abstract : Objective: To examine the impact of critical care on future alcohol-related behaviour. Further, it aimed to explore patterns of recovery for patients with and without alcohol use disorders beyond the hospital environment. Design: In-depth, semistructured interviews with participants (patients) 3–7 months post intensive care discharge. Setting: The setting for this study was a 20-bedded mixed intensive care unit (ICU), in a large teaching hospital in Scotland. On admission, patients were allocated to one of the three alcohol groups: low risk, harmful/hazardous and alcohol dependency. Participants: 21 participants who received mechanical ventilation for greater than 3 days were interviewed between March 2013 and June 2014. Interventions: None. Measurements and main results: Four themes which impacted on recovery from ICU were identified in this patient group: psychological resilience, support for activities of daily living, social support and cohesion and the impact of alcohol use disorders on recovery. Participants also discussed the importance of personalised goal setting and appropriate and timely rehabilitation for alcohol-related behaviours during the critical care recovery period. Conclusions: There is a significant interplay between alcohol misuse and recovery from critical illness. This study has demonstrated that at present, there is a haphazard approach to rehabilitation for patients after ICU. A more targeted rehabilitation pathway for patients leaving critical care, with specific emphasis on alcohol misuse if appropriate, requires to be generated.